Effect of stress on activation during the formation of np junction in co-implanted germanium - Rashid,NN; Aziz,UA; Aid,SR; Akira,S; Ikenoue,H; Xie,F; Centeno,A (2018)
Higher carrier mobility in germanium has made germanium as a favorable candidate to replace silicon as a device substrate for a high-performance device. Further optimization on fabrication process parameters in germanium involving ion-implantation and thermal annealing is important to form a highly activated np junction. Co-implantation technique has prompted interest due to its reported stress-induced activation; which may be due to the implementation of two atoms different in size. Combining with ultra-fast/high temperature of laser thermal annealing may promotes the improvement in activation and damage removal. This works focused on introducing stress to the germanium substrate through co-implantation of dopant ions, follows by laser thermal annealing to activate and remove the implanted damages. It is found that Raman shift of the annealed co-implanted sample can be observed with 0.2% increase in the strain value, when comparing to the single implanted sample. 12% improvement of sheet resistance can also be observed, which may be related due to the increase in stress.